« La bru Gemotsang s’est fait teindre en blond » - Françoise Robin (Ateliers d'Anthropologie)
This article explores how an attentive reading of contemporary Tibetan literature makes it possible to describe the evolutions of female hairstyles and, by extension, the socioeconomic upheavals affecting today’s Tibetan young women. By examining a poem, “The Gemotsang Daughter-in-Law Got Her Hair Dyed Blonde” by Chen Metak (2012), we see how the apparently trivial theme of the dying of the hair of a young woman who goes into the city has a sideration effect on the inhabitants of a village. In the light of these evolutions as perceived by male writers, a few writings by female Tibetan intellectuals are also summoned, and these call for the traditional capillary norms imposed on women to be questioned, linking them with invisible but powerful symbols of subordination.